Maritime navigation and radiocommunication equipment and systems. Global navigation satellite systems (GNSS). BeiDou navigation satellite system (BDS). Receiver equipment. Performance requirements, methods of testing and required test results Part 5, (14th May 2020) - British Standards Institution,
No abstract available